2022
DOI: 10.1088/1361-648x/ac56a7
|View full text |Cite
|
Sign up to set email alerts
|

Non-Markovian systems out of equilibrium: exact results for two routes of coarse graining

Abstract: Generalized Langevin equations (GLEs) can be systematically derived via dimensional reduction from high-dimensional microscopic systems. For linear models the derivation can either be based on projection operator techniques such as the Mori-Zwanzig (MZ) formalism or by “integrating out” the bath degrees of freedom. Based on exact analytical results we show that both routes can lead to fundamentally different GLEs and that the origin of these differences is based inherently on the non-equilibrium nature of the mi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(23 citation statements)
references
References 65 publications
1
22
0
Order By: Relevance
“…In future work, it could be useful to attempt a similar derivation as in [29] using the Mori-Zwanzig projection operator method to derive the GLE but crucially including also the derivation of the memory kernel. This could be done, e.g., by taking advantage of very recent advances in the field of memory kernel-reconstruction techniques for systems out of equilibrium [37,60].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In future work, it could be useful to attempt a similar derivation as in [29] using the Mori-Zwanzig projection operator method to derive the GLE but crucially including also the derivation of the memory kernel. This could be done, e.g., by taking advantage of very recent advances in the field of memory kernel-reconstruction techniques for systems out of equilibrium [37,60].…”
Section: Discussionmentioning
confidence: 99%
“…Shear-flow systems have been studied as examples of driven systems to investigate the validity of fluctuationdissipation relations out of equilibrium [23,31,32]. It was found that the first fluctuation-dissipation theorem (FDT) is different from the equilibrium case [32][33][34][35] but, on the other hand, according to some recent studies [36,37], the second FDT should be valid even far from equilibrium. For this reason, the second FDT allows one to study some properties of a system even in more general cases such as far from equilibrium.…”
Section: Introductionmentioning
confidence: 99%
“…In this section, we briefly review recent advances in both of these directions. More detailed perspectives for each approach can be found in refs ( 332 ) and ( 333 ) for molecular CG modeling at equilibrium and in ref ( 334 ) for out of equilibrium conditions. Furthermore, ref ( 335 ) provides a general review of CG modeling for both in and out of equilibrium conditions.…”
Section: Dynamics Of the Coarse-grained Modelsmentioning
confidence: 99%
“…Important conclusions from these studies are that the 2FDT is no longer generally valid in such cases: namely, in the presence of non-linear or stochastic interactions, 45,46 external forces, or general non-equilibrium settings. 47 Furthermore, additional terms in this relation can emerge. 35,36,45,48 In this work we will take a complementary approach and use the GLE (1) as a starting point to extract effective equations of motion for the coarse-grained variables from microscopic simulations.…”
Section: Introductionmentioning
confidence: 99%
“…What happens in active systems far from equilibrium? This question has been intensely discussed in the literature, 19,22,23,47,49,[53][54][55][56][57] often focusing on the question of whether the 2FDT is still fulfilled. However, as mentioned above, one has some freedom as to how to distribute the net bath forces between the different terms of the GLE.…”
Section: Introductionmentioning
confidence: 99%